Črni bor kot črna kuga - Remec, Meta (Prispevki za novejšo zgodovino, 2021)
The contribution focuses on the attitudes of the local population towards the afforestation with black pine and the creation of large-scale non-native monoculture plantations in the Slovenian Karst. The process, which started at the initiative of the forestry profession and the authorities, provoked considerable opposition from landowners and users of common land who did not want forests there, as they saw them as contrary to their economic interests and established practices. As long as afforestation took place on municipal land, the population still supported it, in principle. However, the encroachment on private land provoked resistance. The locals increasingly resisted the hard labour as well as deliberately destroyed the plantations. After World War II, however, the authorities expected a change in this attitude, as reforestation was ascribed with an extremely strong ideological component. The reforestation of the Karst was supposed to become a symbol of the struggle for a better future, a proof of the power and will of the new society, capable of reversing the consequences of centuries of foreign exploitation in just a few years. Eventually, black pine indeed became an integral part of the landscape and identity of the local population. However, the excitement among the people quickly subsided, as black pine failed to deliver the promised returns and benefits. For the landowners, reforestation, which was considered a success story by forestry experts, represented a disaster and a reason for economic ruin, while accelerated overgrowth mainly took place due to the rapid industrialisation and abandonment of agricultural land.
Keywords: črni bor; gozd; gozdarstvo; Kras; monokulturni nasadi; okoljska zgodovina; pogozdovanje; tujerodne drevesne vrste